Paulo Freire and Social Movements: An Analysis of the Brazilian Scenario - Godoy Stênico, Joselaine Andréia de (2017)
This paper presents the thought of Paulo Freire as a perspective of analysis andreflection on the social movement in Brazilian society. It is action and object ofthis reflection to contribute to the task of reinventing the critical pedagogy in theconstruction of social movements. This is a qualitative research that is dividedinto two stages: the first is dedicated to presenting the theoretical framework,and then an analysis of Brazilian social movements, exposing the origin of thestruggles and advanced to the most recent discussions that have undertaken theBrazil in search of freedom and justice in the recovery of stolen humanity. Anincessant struggle that calls for Liberation Pedagogy developed by Freire, key toolin awareness process, and thus the constitution of social movements.